Reputasi Brand “Wonderful Indonesia” Saat Pandemi Covid-19 - Siti Jhe Chotijah; Diyah Indiyati; Hartin Nur Khusnia; Muhlis Muhlis (Universitas Mataram, 2020)
Wonderful Indonesia as national brand Tourism Indonesia has built such a reputation through communication and branding activities. In 2018, Wonderful Indonesia has ranked 47th in the world, beating its closest competitors, Truly Asia Malaysia and Amazing Thailand. This brand has been able to compete with 180 countries in the world by winning more than 40 awards over the past 3 years and encouraging tourism growth through foreign tourist visits and foreign exchange earnings. During the pandemic covid19 tourism became the worst sector not only in Indonesia but in the world. Maintaining reputation and brand becomes very important in pandemic conditions as an effort to maintain the market. Kemenparekraf as a state agency in charge of tourism issued a policy for the use of contextual logos during a pandemic namely